2022
DOI: 10.1021/acsmedchemlett.2c00052
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a High Affinity Adenosine A1/A3 Receptor Antagonist with a Novel 7-Amino-pyrazolo[3,4-d]pyridazine Scaffold

Abstract: Here we describe the design and synthesis of pyrazolo[3,4- d ]pyridazines as adenosine receptor (AR) ligands. We demonstrate that the introduction of a 3-phenyl group, together with a 7-benzylamino and 1-methyl group at the pyrazolopyridazine scaffold, generated the antagonist compound 10b , which displayed 21 nM affinity and a residence time of ∼60 min, for the human A 1 R, 55 nM affinity and a residence time of ∼73 min, for the human A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We also included the mutant T257 6.58 A since we have previously shown that this residue is a good discriminator between different A 1 R agonists . We did not consider mutations of N254 6.55 or F171 ELC2 since these are known to prevent ligand binding to the A 1 R (including CA200645) and therefore cannot be studied. , Furthermore, we did not consider mutating T270 7.35 since, when we compared the sequences of the hA 1 R and the rA 1 R, we observed that, in the rA 1 R, the equivalent residue at position T270 7.35 is an Ile. Comparison of the binding affinities (p K i ) for 20 and 27 between the hA 1 R and the rA 1 R shows that 20 is equipotent between the two species while 27 has reduced affinity at the rA 1 R (p K i (hA 1 R) = 7.55 ± 0.11; p K i (rA 1 R) = 6.94 ± 0.08).…”
Section: Resultsmentioning
confidence: 99%
“…We also included the mutant T257 6.58 A since we have previously shown that this residue is a good discriminator between different A 1 R agonists . We did not consider mutations of N254 6.55 or F171 ELC2 since these are known to prevent ligand binding to the A 1 R (including CA200645) and therefore cannot be studied. , Furthermore, we did not consider mutating T270 7.35 since, when we compared the sequences of the hA 1 R and the rA 1 R, we observed that, in the rA 1 R, the equivalent residue at position T270 7.35 is an Ile. Comparison of the binding affinities (p K i ) for 20 and 27 between the hA 1 R and the rA 1 R shows that 20 is equipotent between the two species while 27 has reduced affinity at the rA 1 R (p K i (hA 1 R) = 7.55 ± 0.11; p K i (rA 1 R) = 6.94 ± 0.08).…”
Section: Resultsmentioning
confidence: 99%
“…Antagonism of hA 3 R could have important clinical implications as observed by clinical trials for the treatment of glaucoma, ulcerative colitis, psoriasis, and nonalcoholic steatohepatitis (NASH) 9 . As such, we have sought a specific workflow that enables further optimization of hA 3 R antagonists, , e.g., A17 and other leads that we have previously described …”
Section: Discussionmentioning
confidence: 99%
“…Regarding the binding interactions of ligands and the orthosteric binding area exploration, in previous works, we used homology models of the intermediate-active or -inactive hA 3 R generated from the experimental structure of the inactive hA 2A R in complex with either an agonist or antagonist . We were able to investigate the binding profiles of high efficacy agonists and subtype-selective antagonists. ,,, Furthermore, through the combination of MD simulations and mutagenesis experiments, we were able to explore the interactions between these ligands and both “wild-type” (WT) or mutated hA 3 Rs …”
Section: Introductionmentioning
confidence: 99%
“…As such, we have sought a specific workflow that enables further optimization of hA3R antagonists, 86,102 e.g., A17 45 and other leads that we have previously described. 85 We have retrospectively applied a computational drug binding analysis for the 3,5-disubstituted-7-(phenylamino)-pyrazolo[3,4-c]pyridine antagonists L3-L6, L9, Α17 to describe their kinetic and thermodynamic binding profile and to select an appropriate homology model. We explored the thermodynamic and kinetic binding SARs of these antagonists against inactive hA3R using TI/MD calculations of relative binding free energies and τRAMD calculations of relative RTs in comparison with RTexps and by testing available homology models of inactive hA3R.…”
Section: Discussionmentioning
confidence: 99%
“…42 We were able to investigate the binding profiles of high efficacy agonists 47 and subtype selective antagonists. 34,48,49,85 . Furthermore through combination of MD simulations and mutagenesis experiments we were able to explore the interactions between these ligands and both 'wild-type' (WT) or mutated hA3Rs.…”
Section: Introductionmentioning
confidence: 99%